Reversibility of pancreatic β-cells dysfunction after vitamin D and calcium supplementation: a pilot study in a population of obese and prepubescent North-African children. Issue 1 (31st December 2022) - Gaddas, Meriem; Latiri, Imed; Kebaili, Raoudha; Kacem, Ilhem; Jaballah, Nesrine; Maatoug, Jihene; Salaani, Mohamed; Boughammoura, Lamia; Ben Saad, Helmi
ABSTRACT: The mechanisms of diabetogenesis in children remain largely obscure. This study aimed to determine the impact of vitamin D and calcium supplementation on pancreatic β-cells function in terms of insulin secretion and sensitivity. This was a quasi-experimental study involving 30 obese and prepubescent Tunisian children (57% boys). During three months, the children received calcium and vitamin D supplementation at therapeutic doses. An oral glucose tolerance test (OGTT) was performed at the beginning and at the end of the study. The following metabolic definitions were applied: i) hyperinsulinism: insulinemia sum > 300 μ UI/ml during OGTT, ii) insulin-resistance: homeostatic model assessment of insulin-resistance > 2, iii) normal glycaemic profile: normal plasma levels during OGTT without any spike, and iv) pancreatic β-cells dysfunction reversibility: disappearance of the aforementioned disorders. The means ± standard-deviation of age and body mass index were 10.87 ± 1.9 years, and 30.17 ± 4.99 kg/m 2, respectively. All children were at the stage of hyperinsulinism associated with insulin-resistance. These disturbances were noted even in children having a normal glycaemic profile at OGTT. After calcium and vitamin D supplementation, glycaemic profile as well as insulin-secretion improved significantly ( p < 0.0001 ). Hyperinsulinism and insulin-resistance decreased significantly by 56.67% ( p < 0.0001 ) and 70.00% ( p < 0.0001 ), respectively. Complete reversibility of these two disorders was noted in 26.6% of children. To conclude, in obese and prepubescent children, vitamin D and calcium supplementation led to the reversibility of the pancreatic β-cells dysfunction.